Localized Epidermal Cysts as a Radiation Recall Phenomenon in a Melanoma Patient Treated with Radiotherapy and the BRAF Inhibitor Vemurafenib - Carine Houriet; Natalie D. Klass; Helmut Beltraminelli; Luca Borradori; Patrick A. Oberholzer (Karger Publishers, 2014)
BRAF inhibitors are broadly used for metastatic melanoma with BRAF mutations. Their use results in various cutaneous side effects, such as the development of keratoacanthomas and squamous cell carcinomas. We report a patient with metastatic melanoma treated with vemurafenib who developed dozens of histologically confirmed epidermal cysts within 2 months after initiation of vemurafenib administration. The cystic lesions were observed only in the localized area where a large exophytic melanoma tumor mass had been previously irradiated. Localized epidermal cysts may constitute an unusual radiation recall reaction in patients treated with BRAF inhibitors.